A pattern of violence: how the law classifies crimes and what it means for justice - Sklansky, David A. (The Belknap Press of Harvard University Press, 2021)
"Before the 1960s, the distinction between violent and nonviolent crime played hardly any role in the law. Since then, the number of crimes deemed violent has skyrocketed. David Alan Sklansky shows how shifting and inconsistent legal definitions of violence have fueled mass incarceration, protected abusive police, and undermined criminal justice"--